Sistem penerapan absensi online (Aplikasi Bravo) dalam efektivitas meningkatkan kedisiplinan pegawai Di BBWS Pemali Juana - Kasan, Ahmad; Abdullah, Lukman Zaini; Apriliyanto, Nanang (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2024)
This study aims to analyze how the implementation of an online attendance digitization system through the Bravo application can increase the effectiveness of employee discipline at the Pemali Juana River Basin Agency (BBWS). This research uses a qualitative method and is carried out on employees in the BBWS Pemali Juana Environment. Research based on the theory of George C. Edwards III, namely the strategy in implementing onlien attendance, there are 4 things, namely: communication, resources, disposition and bureaucratic structure, and in assessing the effectiveness of online applications based on Sleerk's theory, 2018, the effectiveness of implementing online attendance can be seen from 5 values, namely increased productivity, practical, efficient, transparency and high level of security.The results showed that the application of the Bravo application has had a positive influence on employee discipline. Some of the factors that support this increase in discipline include ease of access, system transparency and increasing disciplinary motivation. From the analysis, information was also obtained that BBWS Pemali Juana implemented online attendance through the BRAVO application through delivery in the form of socialization, video tutorials, official memos, and government regulations to improve discipline through BRAVO attendance. From some of these things, BBWS Pemali Juana has succeeded in increasing the level of employee discipline which can be seen from the comparison data of fingerprint attendance in 2019 with the use of online attendance in 2023.